Starlikeness of General Integral Operator for Meromorphic Multivalent Functions. (30th January 2013) - Goswami, Pranay; Bulut, Serap
Abstract : We introduce a new integral operator ℐ γ, δ p ( f 1, …, f n ) for meromorphic multivalent functions. The starlikeness condition of this integral operator is determined. Several special cases are also discussed in the form of corollaries.